PRODUKTIVITAS DAN EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHATANI PADI DI DESA SRIKATON KECAMATAN BUAY MADANG TIMUR - Dimas Adi Saputra; Tinjung Mary Prihtanti (Universitas Galuh, 2022)
The efficiency of the use of inputs in the farming field in the effort to reach an optimal profit in the farming field and the environment continuity in agriculture. The correct inputs placement will increase the efficiency and productivity in the rice farming field. This research aims to analyze the impact of the use of seeds, urea, phonska, sp36, pesticides, and labor on the productivity of rice farming and the efficiency level in the use of production factors in the rice farming field in Desa Srikaton, Buay Madang Timur District, East OKU Regency. The quantitative method is used in this research. The data are collected by using questionnaire. There are 60 participants which are determined by cluster sampling technique. Primary and secondary data are used as supporting data. The data are analyzed by using regression technique, using Cobb-Douglas production function model, and allocative efficiency analysis. The result shows that urea, phonska, pesticides, and labor had a positive impact on rice production, while seeds and sp36 had no effect on rice production. In Desa Srikaton rice farming field, the production inputs such as seeds, urea, sp36, pesticide, and labor have not efficient yet, while production inputs such as phonska fertilizer are not efficient.